Factors Contributing to Household Dietary Diversity. - Sharma, Sriju. (Tufts University. Tisch Library., 2020)
This poster explores the relationships between HH Dietary Diversity Score (HDDS) and HH characteristics.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy